MISADVENTURES OF ECONOMIC HISTORY IN MODERN RUSSIAN HIGHER SCHOOL: “WHO IS IN FAULT” AND “WHAT IS TO BE DONE”? - Dmitry Y. Maidachevsky (Высшее образование в России, 2022)
Erstwhile the inherent subject of economists’ training program, now Economic History has in all but name disappeared from the universities’ curriculum in the view of historical redundancy. The strategies of the disciplinary status sustention of Economic History should be directed on the knowledge-based independence substantiation of the discipline per se as the field of Economics.